ARTIKEL REVIEW: BAKTERI ENDOFIT SEBAGAI SUMBER SENYAWA ANTIMIKROBA - Rahma, Nadika (Jurnal Biogenerasi, 2026)
Antimicrobial resistance is a global problem that drives the search for new sources of antimicrobial compounds. One potential source that has been widely studied is endophytic bacteria, which are microorganisms that live within plant tissues without causing disease. This review aims to examine the potential of endophytic bacteria as a source of antimicrobial compounds based on national and international scientific literature. The review was conducted through an analysis of relevant research articles in the field of microbiology. The findings indicate that endophytic bacteria, particularly from the genera Bacillus, Pseudomonas, and Streptomyces, are capable of producing various bioactive secondary metabolites, including alkaloids, antimicrobial peptides, polyketides, and phenolic compounds. These metabolites have demonstrated inhibitory activity against pathogenic microorganisms. The production of antimicrobial metabolites is influenced by host plant species and environmental conditions. Therefore, endophytic bacteria have strong potential to be developed as a source of natural antimicrobials to address antibiotic resistance, although further studies are required to evaluate production optimization and safety.